Meta‐analysis evaluating music interventions for anxiety and pain in surgery - Kühlmann, A. Y. R.; de Rooij, A.; Kroese, L. F.; van Dijk, M.; Hunink, M. G. M.; Jeekel, J. (British journal of surgery, 2018)
Background This study aimed to evaluate anxiety and pain following perioperative music interventions compared with control conditions in adult patients. Methods Eleven electronic databases were searched for full‐text publications of RCTs investigating the effect of music interventions on anxiety and pain during invasive surgery published between 1 January 1980 and 20 October 2016. Results and data were double‐screened and extracted independently. Random‐effects meta‐analysis was used to calculate effect sizes as standardized mean differences (MDs). Heterogeneity was investigated in subgroup analyses and metaregression analyses. The review was registered in the PROSPERO database as CRD42016024921. Results Ninety‐two RCTs (7385 patients) were included in the systematic review, of which 81 were included in the meta‐analysis. Music interventions significantly decreased anxiety (MD –0·69, 95 per cent c.i. –0·88 to –0·50; P < 0·001) and pain (MD –0·50, –0·66 to –0·34; P < 0·001) compared with controls, equivalent to a decrease of 21 mm for anxiety and 10 mm for pain on a 100‐mm visual analogue scale. Changes in outcome corrected for baseline were even larger: MD –1·41 (–1·89 to –0·94; P < 0·001) for anxiety and –0·54 (–0·93 to –0·15; P = 0·006) for pain. Music interventions provided during general anaesthesia significantly decreased pain compared with that in controls (MD –0·41, –0·64 to –0·18; P < 0·001). Metaregression analysis found no significant association between the effect of music interventions and age, sex, choice and timing of music, and type of anaesthesia. Risk of bias in the studies was moderate to high. Conclusion Music interventions significantly reduce anxiety and pain in adult surgical patients. Effective